IgE Reactivity from Serum of Blomia Tropicalis Allergic Patients to the Recombinant Protein Blo t 1 - Fonseca-Fonseca, Lisandra; Díaz, Ana María (Puerto Rico Health Sciences Journal, 2011)
see manuscript